Crystallization and preliminary X‐ray crystallographic studies of DnaJ from Streptococcus pneumoniae. Issue 3 (24th March 2013) - Zhao, Shasha; Jin, Li; Niu, Siqiang; Yang, Wei; Zhang, Shaocheng; Guo, Zhen; Zhang, Hongpeng; Huang, Ailong; Yin, Yibing; Wang, Deqiang
<x xml:space="preserve">Abstract</x> DnaJ, cooperating with DnaK and GrpE, promotes the folding of unfolded hydrophobic polypeptides, dissociates protein complexes and translocates protein across membranes. Additionally, DnaJ from Streptococcus pneumoniae (SpDnaJ) is involved in the infectious disease process and is being developed as a potential vaccine to prevent bacterial infection. Here the expression, purification, crystallization and preliminary crystallographic analysis of SpDnaJ are reported. The crystals belong to space groups I222 or I212121 and the diffraction resolution is 3.0 Å with unit‐cell parameters a = 47.68, b = 104.45, c = 234.57 Å. The crystal most likely contains one molecule in the asymmetric unit, with a VM value of 3.24 Å3 Da−1 and a solvent content of 62.1%.